2003
DOI: 10.1038/sj.ijo.0802516
|View full text |Cite
|
Sign up to set email alerts
|

Multiple linked mouse chromosome 7 loci influence body fat mass

Abstract: BACKGROUND: Congenic mouse strains contain donor mouse strain DNA in genomes otherwise identical to a background strain. They can be used to identify defined chromosomal regions containing obesity genes with small effects. OBJECTIVE: The objective of this study was to discover congenic strains containing genes that influence body fat in mice and to examine interactions between these genes. DESIGN: A survey of congenic strains showed that the B6.C-Tyr c H1 b Hbb d /By (B6.C-H1) congenic strain, with a 24 centiM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
5
40
0
Order By: Relevance
“…71 Thus, in addition to clustering of QTL, there is a striking Meta-analysis of QTL for body weight and adiposity S Wuschke et al overlap of these regions with candidate genes and markers implicated in control of body weight and body composition in rodents and humans. QTL mapping of complex traits is a promising technique, and the generation of novel rodent models, congenic and consomic lines [72][73][74][75] as well as application of bioinformatics methods, 76 including comparative genomics and genomewide haplotype analysis have provided progress towards identification of the genes responsible for the effects of a QTL. Our study may provide guidance for a further systematic investigation of candidate genes within the consensus QTL regions, and application of high-density single nucleotide polymorphism (SNP) maps.…”
Section: Discussionmentioning
confidence: 99%
“…71 Thus, in addition to clustering of QTL, there is a striking Meta-analysis of QTL for body weight and adiposity S Wuschke et al overlap of these regions with candidate genes and markers implicated in control of body weight and body composition in rodents and humans. QTL mapping of complex traits is a promising technique, and the generation of novel rodent models, congenic and consomic lines [72][73][74][75] as well as application of bioinformatics methods, 76 including comparative genomics and genomewide haplotype analysis have provided progress towards identification of the genes responsible for the effects of a QTL. Our study may provide guidance for a further systematic investigation of candidate genes within the consensus QTL regions, and application of high-density single nucleotide polymorphism (SNP) maps.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified a B6.C-D7Mit353 subcongenic mouse line with less body fat than its B6By background control line (7). Phenotypic differences (such as obesity) between these background and congenic strains are due to polymorphisms in genes located in the congenic donor region located on chromosome 7.…”
Section: Introductionmentioning
confidence: 99%
“…PRCP initiates the degradation and inactivation of extracellular α-MSH [1][2][3][4][5][6][7][8][9][10][11][12][13] . We found that Prcp was expressed in neuronal populations that send efferents to areas where α-MSH [1][2][3][4][5][6][7][8][9][10][11][12][13] is released from axon terminals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, coupled with the growing evidence that some of the QTL for complex traits consist of multiple closely linked causal genes (Legare and Frankel 2000;Rogner et al 2001;Liu et al 2002;Diament and Warden 2004;Yalcin et al 2004;Flint et al 2005), lead us to hypothesize that the chromosome 6 locus may also represent such a multigenic region. To examine this, we created a panel of overlapping and reciprocal subcongenic lines from CON6.Ldlr À/À mice and characterized each line for development of atheroma in the proximal aorta.…”
mentioning
confidence: 99%